Effects of a novel combination of orlistat and acarbose on tolerability, appetite, and glucose metabolism in persons with obesity - Ulf Holmbäck; Anders Forslund; Stefan Grudén; Göran Alderborn; Arvid Söderhäll; Per M. Hellström; Hans Lennernäs (Wiley, 2020)
Summary Objective There is an unmet medical need for a safe and effective weight loss product with minimal systemic side‐effects. In this study, the effect of a novel modified‐release fixed‐dose combination of orlistat and acarbose (MR‐OA) was compared with conventional orlistat (CO) regarding tolerability, appetite and glucose metabolism. Methods Sixty‐seven men with obesity, aged 24 to 60 years with body mass indexes (BMIs) 33 to 40 kg m−2 or BMIs 30 to 32 kg m−2 and waist circumference above 102 cm were included. They were randomized to either three different doses of the test formulation MR‐OA (60 mg orlistat/20 mg acarbose, 90/30 and 120/40) or CO (Xenical, 120 mg orlistat) for a 2‐week study of daily treatment. The participants spent days 1 and 14 at the clinical research centre where they received standardized meals, had blood sampling and filled in questionnaires regarding tolerability and appetite after meals. In days 2 to 13, the participants were at home and continued to fill in the questionnaires daily. Results In the MR‐OA groups, reports of liquid and oily stools as well as faecal incontinence were fewer, whereas reports of gastric distension and flatulence were higher, compared with the CO group. More participants reported decreased hunger in the 90/30 and 120/40 MR‐OA, and postprandial plasma glucose concentration was reduced in all MR‐OA groups compared with CO. Conclusions This study shows that by using a modified‐release dosage form, orlistat and acarbose can be combined without compromising tolerability. Furthermore, MR‐OA shows promising effects regarding reduction of appetite and reduces postprandial glucose. Tolerability is coupled to compliance and thereby efficacy of a treatment; therefore, this novel combination MR‐OA could be an effective approach for weight loss treatment. A follow‐up study in a more diverse population and for a longer duration with weight loss as primary outcome variable is planned.